Effects of drying methods on the antioxidant activities on Benincasa Hispida seed extracts - Nurhamizah, Ibrahim (2013)
The present study investigated the changes in total phenolic content (TPC) and antioxidant capacity of B.hispida seeds after three drying treatment (sun drying, oven drying and freeze drying) compared to fresh samples by DPPH radical scavenging method and total phenolic content. Ethanol is used as the solvent for extraction because ethanol can obtain the highest antioxidant activity due to its highest polarity. The analysis was conducted in University Malaysia Pahang laboratory using the ultraviolet-visible spectrophotometry. The results of this study showed that the water content, antioxidant activity and total phenolic content which are highest from B.hispida seeds were obtained by freeze drying. Sun drying was the worst in antioxidant capacity and phenolic content because the value obtained are less compared other methods. Overall, B. hispida may have high potential applications in the medical and food industries.